MLearning : Mobile Learning and Performance in the Palm of Your Hand. - Metcalf, David (HRD Press, 2006)
Gain back hours of useful time each day by learning "on the go". The next time you're on the road, stuck in an airport or waiting in line, don't allow your valuable time to be wasted by circumstances you can't control. Turn on your PDA, smart phone or wireless connection and use those "stolen moments" to learn. Mobile learning - or mlearning - combines the technologies of mobile communications with any electronically delivered material. This exciting new book speaks to users at the grassroots level who want to capitalize on the latest mLearning.